Influence of oxygen concentration on the neuroprotective effect of hydrogen inhalation in a rat model of cardiac arrest - Wang, Jianjie; Shen, Yiming; Li, Jingru; Chen, Bihua; Yin, Changlin; Li, Yongqin (Frontiers in Neurology, 2022)
Background Post-cardiac arrest (CA) brain injury is the main cause of death in patients resuscitated from CA. Previous studies demonstrated that hydrogen inhalation mitigates post-CA brain injury. However, factors affecting the efficacy of hydrogen remain unknown. In the present study, we investigated the influence of oxygen concentration and targeted temperature on neuroprotective effect in a CA rat model of ventricular fibrillation (VF). Methods Cardiopulmonary resuscitation (CPR) was initiated after 7 min of untreated VF in adult male Sprague–Dawley rats. Immediately following successful resuscitation, animals were randomized to be ventilated with 21% oxygen and 79% nitrogen (21%O2); 2% hydrogen, 21% oxygen, and 77% nitrogen (2%H2 + 21%O2); 2% hydrogen, 50% oxygen, and 48% nitrogen (2%H2 + 50%O2); or 2% hydrogen and 98% oxygen (2%H2 + 98%O2) for 3 h. For each group, the target temperature was 37.5°C for half of the animals and 35.0°C for the other half. Results No statistical differences in baseline measurements and CPR characteristics were observed among groups. For animals with normothermia, 2%H2 + 50%O2 (123 [369] vs. 500 [393], p = 0.041) and 2%H2 + 98%O2 (73 [66] vs. 500 [393], p = 0.002) groups had significantly lower neurological deficit scores (NDSs) at 96 h and significantly higher survival (75.0 vs. 37.5%, p = 0.033 and 81.3 vs. 37.5%, p = 0.012) than 21%O2 group. For animals with hypothermia, no statistical difference in NDS among groups but 2%H2 + 98%O2 has significantly higher survival than the 21%O2 group (93.8 vs. 56.3%, p = 0.014). Conclusion In this CA rat model, inhaling 2% hydrogen combined with a high concentration of oxygen improved 96-h survival, either under normothermia or under hypothermia.